Is it Important for Elementary School Students to Learn the Basics of Finance? - Yunikawati, Nur Anita; Priambodo, Magistyo Purboyo; Puspasari, Emma Yunika; Istiqomah, Ni’matul (KnE Social Sciences, 2021)
Financial education is very important at all levels of education, even at the level of basic education. The purpose of this study was to determine the importance of elementary school students mastering the basic knowledge of finance. This study was conducted from May to October 2019 at SDN 1 Gandusari, Blitar Regency, East Java Province, Indonesia, and used a qualitative case study research method. This study used primary data in the form of interviews, focus group discussions (FGD) and documentation. The findings revealed the financial profile of SDN 1 Gandusari students as well as the financial behavior of students in daily life. Based on the results, it is important for policymakers, academics and practitioners in the field of basic education to include their own curriculum for financial education for elementary school students. Keywords: elementary school student, learn, basics of finance